SPESIASI DAN BIOAVAILABILITAS LOGAM Pb DALAM SEDIMEN DI KAWASAN PESISIR SANUR - Meita Sari, Sri Dian; Gede Bawa, I Gusti Agung (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 8 No 1 (2014), 2014)
Total content of Pb metal in sediments has been reported or published frequently, but it could not provide information about various forms of metals contained in sediments and did not show the true metal concentrations involved in the process of bioaccumulation by organisms. Therefore, this study was aimed to determine the bioavailability of Pb metal and speciation the metal in various forms or compounds existing in the sediments. A quantitative analysis of total metal content, Pb in the sediments was initiated performing the digestion method using the mixture of HNO3 and HCl (3:1) in ultrasonic bath at 60 0C for 45 minutes, and continued heating on a hotplate for another 45 minutes at 140 0C. Moreover, analysis of Pb metals as bioavailability fraction was perfomed by single extraction method of EDTA and HCl, while for metal speciation fractions on each phase using Sequential Extraction Technique. Consequently, the metal concentrations of digestion and extraction solutions were measured by using an atomic absorption spectroscopy (AAS) technique with the aplication of calibration method. The total concentrations of Pb in sediments collected from Sanur Beach ranged from 139,9945 to 260,1521 mg/kg. The highest bioavailability of Pb obtained in sediments at site II (Sindhu Beach), in which the Pb extracted from sediments was 21.44%. Generally, the Pb metal associated in the sediments at Sanur Beach was bounded in oxidisable organic fraction (2.08 – 3.50%).
Keywords: speciation, bioavailability, Pb metal, sediment, Sanur Beach